Thermally conductive two-component addition curing type silicone composition, cured product, and sheet

The thermally conductive two-component silicone composition addresses viscosity and elongation issues by optimizing filler blends, ensuring high thermal conductivity and flexibility, suitable for heat dissipation in electronic components under high temperature and humidity.

JP2024178019APending Publication Date: 2024-12-24SHIN ETSU CHEMICAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023096502
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing thermally conductive compositions face challenges with high viscosity due to increased filler content, leading to handling difficulties and reduced elongation, which affects their ability to follow the warpage of electronic components, especially under high temperature and humidity conditions.

Method used

A thermally conductive two-component addition-curing silicone composition is developed, comprising specific blends of spherical aluminum oxide powders with varying particle sizes and a silane coupling agent, optimized to maintain low viscosity and high thermal conductivity while ensuring moisture resistance and flexibility.

Benefits of technology

The composition achieves high thermal conductivity, maintains low hardness, and exhibits excellent elongation, allowing it to effectively dissipate heat from electronic components even under harsh conditions, enhancing reliability and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178019000001
    Figure 2024178019000001
  • Figure 2024178019000002
    Figure 2024178019000002
  • Figure 2024178019000003
    Figure 2024178019000003
Patent Text Reader

Abstract

To provide a highly thermal conductive two-component addition curing type silicone composition having high thermal conductivity and high moisture resistance, and a cured product thereof.SOLUTION: A thermally conductive two-component addition curing type silicone composition comprises a first liquid and a second liquid, the composition comprising (A) an organopolysiloxane having an alkenyl group, (B) an organohydrogenpolysiloxane, (C) a thermally conductive filler including spherical aluminum oxide powders (C-1)-(C-4) having specific average particle diameters and a spherical or irregular-shaped aluminum oxide powder (C-5) having a specific average particle diameter, (D) a silane coupling agent and / or an organopolysiloxane represented by general formula (1), and (E) a platinum catalyst, wherein the first liquid does not contain the component (B), the second liquid does not contain the component (E), and the components (A) to (E) are included at a specific ratio in the entire composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermally conductive two-part addition-curable silicone composition, a cured product, and a sheet. [Background technology]

[0002] It is widely known that heat-generating electronic components generate heat during use and the resulting performance degradation, and various heat dissipation technologies are used as a means to solve this problem. In general, a cooling member (such as a heat sink) is placed near the heat-generating part, and the two are placed in close contact with each other, and the heat is efficiently removed from the cooling member to dissipate heat. In this case, if there is a gap between the heat-generating part and the cooling member, the heat conductivity decreases due to the presence of air with poor thermal conductivity, and the temperature of the heat-generating part does not decrease sufficiently. To prevent this phenomenon, heat-dissipating materials with good thermal conductivity and conformability to the surface of the part, such as heat-dissipating grease and heat-dissipating sheets, are used.

[0003] In recent years, the amount of heat generated by mounted components has been increasing due to the miniaturization and high density of electronic devices. For example, the amount of heat generated by CPUs (Central Processing Units) and GPUs (Graphics Processing Units) has increased as their performance has improved. In order to keep operating temperatures low and maintain high performance, heat dissipation materials used as heat countermeasures are required to have high heat dissipation performance.

[0004] In addition, since the GPUs used in ADAS (Advanced Autonomous Driving Assistance Systems) are used in vehicles, the heat dissipation materials used to deal with the heat from the GPUs are required to be insulating and highly reliable. Examples of thermally conductive fillers used in heat dissipation materials include aluminum oxide, aluminum nitride, and magnesium oxide, which are insulating and have high thermal conductivity. However, while aluminum nitride and magnesium oxide have a higher thermal conductivity than aluminum oxide, they have the problem of being highly hygroscopic and becoming strongly alkaline when absorbing moisture.

[0005] As an example of a thermally conductive resin composition using aluminum oxide as a thermally conductive filler, there is given a highly thermally conductive resin composition using spherical aluminum oxide powder with an average particle size of 10 to 50 μm and with specified average sphericity and hydroxyl group content, and aluminum oxide powder with an average particle size of 0.3 to 1 μm, with the respective volumetric blending ratios and filling amounts specified; however, sufficient thermal conductivity could not be obtained with a filler with a maximum average particle size of 50 μm (Patent Document 1: Japanese Patent No. 5755977).

[0006] Also, examples include compound particles for high thermal conductive resin compounds containing 60 to 80 volume % of spherical alumina particles having an average particle size of 80 to 100 μm and 20 to 40 volume % of non-spherical alumina particles having an average particle size of 0.5 to 7 μm, and a high thermal conductive resin compound containing 60 to 85 volume % of these particles by volume. However, when a large amount of alumina particles with a large average particle size is contained, there are problems in that oil separation occurs over time and viscosity increases (Patent Document 2: Japanese Patent No. 5085050).

[0007] Also, an example of a highly thermally conductive silicone composition has been given that contains a total of 80 to 90 volume % of spherical aluminum oxide particles having an average particle diameter of 50 to 150 μm and spherical or irregular aluminum oxide particles having an average particle diameter of 0.5 to 7 μm, and that the volume ratio of the spherical aluminum oxide particles having an average particle diameter of 50 to 150 μm to the spherical or irregular aluminum oxide particles having an average particle diameter of 0.5 to 7 μm is 5:5 to 9.5:0.5. However, this composition contains a large amount of a silane coupling agent for organopolysiloxane, and there is a problem in that there is a significant increase in hardness and a decrease in elongation under high temperature and high humidity conditions (Patent Document 3: Japanese Patent No. 6648837). [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent No. 5755977 [Patent Document 2] Patent No. 5085050 [Patent Document 3] Patent No. 6648837 Summary of the Invention [Problem to be solved by the invention]

[0009] In order to obtain a high thermal conductivity, it is possible to increase the proportion of the thermally conductive filler in the thermally conductive composition, but increasing the proportion of the thermally conductive filler increases the viscosity and makes the composition less easy to handle. In addition, when the proportion of the thermally conductive filler is increased, it is necessary to increase the proportion of the silane coupling agent or the organopolysiloxane having an alkoxy group at one end that treats the surface of the thermally conductive filler. These silane coupling agents and organopolysiloxanes are thought to condense under moisture-resistant conditions, and if a large amount of these are contained in the thermally conductive composition, this causes the hardness of the cured product of the thermally conductive composition to increase under moisture-resistant conditions. The cured product of the thermally conductive composition with increased hardness has a reduced elongation and cannot follow the warping of the substrate, resulting in a reduced reliability as a heat dissipation material.

[0010] In addition, unlike one-component addition-curing heat-dissipating materials, two-component addition-curing materials are characterized by their room-temperature storage properties, and because dehydrogenation of the organohydrogenpolysiloxane by the thermally conductive filler can occur during storage at room temperature, it is necessary to suppress dehydrogenation by reducing the activity of the surface through surface treatment of the thermally conductive filler. Therefore, it is necessary to use an appropriate amount of silane coupling agent or organopolysiloxane having an alkoxy group at one end in order to improve the room-temperature storage properties of two-component addition-curing heat-dissipating materials.

[0011] The present invention has been made in view of the above circumstances, and has as its object to provide a highly thermally conductive two-part addition-curable silicone composition that has both high thermal conductivity and high moisture resistance. [Means for solving the problem]

[0012] As a result of intensive research by the present inventors to solve the above problems, it has been found that a first liquid containing an alkenyl group-containing organopolysiloxane, a spherical aluminum oxide powder having an average particle diameter of 80 to 120 μm, a spherical aluminum oxide powder having an average particle diameter of 60 to 80 μm, a spherical aluminum oxide powder having an average particle diameter of 25 to 60 μm, a spherical aluminum oxide powder having an average particle diameter of 5 to 25 μm, and a spherical or irregular aluminum oxide powder having an average particle diameter of 0.1 to 5 μm is blended in specific amounts and specific ratios, and a silane coupling agent and / or an organopolysiloxane having a hydrolyzable group and a platinum catalyst for hydrosilylation reaction, an alkenyl group-containing organopolysiloxane, and a silane coupling agent and / or a first liquid containing a platinum catalyst for hydrosilylation reaction, The inventors have found that the above-mentioned problems can be solved by a thermally conductive two-part addition-curable silicone composition comprising specific amounts and ratios of an organohydrogenpolysiloxane having hydrogen atoms bonded to element atoms, a spherical aluminum oxide powder having an average particle diameter of 80 to 120 μm, a spherical aluminum oxide powder having an average particle diameter of 60 to 80 μm, a spherical aluminum oxide powder having an average particle diameter of 25 to 60 μm, a spherical aluminum oxide powder having an average particle diameter of 5 to 25 μm, and a spherical or irregular aluminum oxide powder having an average particle diameter of 0.1 to 5 μm, and a second part containing a silane coupling agent and / or an organopolysiloxane having a hydrolyzable group, which has been mixed together, and have completed the present invention.

[0013] That is, the present invention is a thermally conductive two-part addition-curable silicone composition comprising a first part and a second part, (A) an organopolysiloxane having at least two alkenyl groups bonded to silicon atoms in each molecule; (B) an organohydrogenpolysiloxane having at least two hydrogen atoms bonded to silicon atoms in each molecule; (C) A thermally conductive filler comprising spherical aluminum oxide powder (C-1) having an average particle size of 80 μm or more and 120 μm or less, spherical aluminum oxide powder (C-2) having an average particle size of 60 μm or more and less than 80 μm, spherical aluminum oxide powder (C-3) having an average particle size of 25 μm or more and less than 60 μm, spherical aluminum oxide powder (C-4) having an average particle size of 5 μm or more and less than 25 μm, and spherical or irregular aluminum oxide powder (C-5) having an average particle size of 0.1 μm or more and less than 5 μm, (D) a silane coupling agent and / or a compound represented by the following general formula (1): [ka] (In the formula, R 1 are independently monovalent hydrocarbon groups; R 2 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group, or an acyl group, a is a positive number of 5 to 100, and b is an integer of 1 to 3. Organopolysiloxanes represented by the formula: (E) Platinum catalyst for hydrosilylation reaction Among the components (A) to (E), the first liquid contains the components (A), (C), (D), and (E) but does not contain the component (B); the second liquid contains the components (A), (B), (C), and (D) but does not contain the component (E); and the entire composition consisting of the first liquid and the second liquid contains 100 to 200 parts by mass of the component (D) per 100 parts by mass of the total of the components (A) and (B). and the composition contains 200 to 600 parts by mass of the component (C-1), 200 to 500 parts by mass of the component (C-2), 200 to 500 parts by mass of the component (C-3), 200 to 500 parts by mass of the component (C-4), and 300 to 700 parts by mass of the component (C-5) relative to 100 parts by mass in total of the components (A), (B), and (D), and the total of the components (C-1) to (C-5) is 1700 to 2000 parts by mass, The present invention provides a thermally conductive two-part addition-curable silicone composition, which is characterized by:

[0014] In such a thermally conductive two-component addition-curable silicone composition, the blending ratio of the thermally conductive filler and the blending amount of the silane coupling agent or organopolysiloxane having an alkoxy group at one end are within appropriate ranges, and when this is cured, a sheet-like cured product having high thermal conductivity and high moisture resistance can be obtained.

[0015] In this case, it is preferable that each of the first liquid and the second liquid has a viscosity at 25° C. of 30 to 800 Pa·s when measured with a spiral viscometer at a rotation speed of 10 rpm.

[0016] If the viscosity is within the above range, the thermally conductive two-part addition curable silicone composition will have a stable shape and will have excellent workability.

[0017] The component (C-5) is preferably an aluminum oxide powder having an irregular shape.

[0018] When the aluminum oxide powder of component (C-5) has an irregular shape, the contact area between the fillers is larger than when the fillers are spherical, which makes it possible to increase the thermal conductivity of the thermally conductive two-part addition curable silicone composition.

[0019] The present invention also provides a cured product of the above-mentioned thermally conductive two-part addition curable silicone composition, wherein the hardness of the sheet-like cured product obtained by curing the thermally conductive two-part addition curable silicone composition is in the range of 20 to 80, as measured using a Shore OO hardness tester as specified in ASTM D 2240-05.

[0020] If the hardness of the sheet-like cured product is within the range of 20 to 80, the cured product becomes a rubber-like product with low hardness, and the possibility that the cured product will come off from the mounted position due to impact such as vibration can be reduced. In addition, the cured product does not apply a large stress to the electronic components in contact with it, so that the solder life of the electronic components is favorable.

[0021] The present invention also provides a cured product of the above-mentioned thermally conductive two-part addition curable silicone composition, wherein the hardness of the sheet-like cured product obtained by curing the thermally conductive two-part addition curable silicone composition is such that after being subjected to 85°C / 85% RH for 1000 hours, the elongation at break measured in a tensile test specified in JIS K 7161 using a tensile No. 2 dumbbell-shaped tensile test piece conforming to JIS K 6251 is 10% or more.

[0022] If the elongation at break of the sheet-shaped cured material in the above tensile test is 10% or more, when the cured material is used as a heat dissipation material, the heat dissipation material will be able to conform to the warping of electronic components that occurs under high temperature and high humidity conditions, and will be able to efficiently remove heat from the electronic components.

[0023] The present invention also provides a thermally conductive sheet obtained by curing the above-mentioned thermally conductive two-part addition curable silicone composition.

[0024] Such a thermally conductive sheet has high thermal conductivity and suppresses the increase in hardness and decrease in elongation of the cured product due to moisture-resistant conditions, making it useful as an excellent heat dissipation material for heat-generating electronic components. Effect of the Invention

[0025] According to the present invention, by using an appropriate blend ratio of the thermally conductive filler and an appropriate amount of the silane coupling agent or the organopolysiloxane having an alkoxy group at one end, it is possible to provide a highly thermally conductive two-part addition curable silicone composition and a cured product having high thermal conductivity and high moisture resistance. The cured product can be used as a heat dissipation material for heat-generating electronic components even under high temperature and high humidity conditions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] As a result of intensive research into solving the above-mentioned problems, the inventors have discovered that a thermally conductive two-part addition curable silicone composition in which each component of the composition is blended in specific amounts and specific ratios can solve the above-mentioned problems, which has led to the creation of the present invention.

[0027] That is, the present invention is a thermally conductive two-part addition-curable silicone composition comprising a first part and a second part, (A) an organopolysiloxane having at least two alkenyl groups bonded to silicon atoms in each molecule; (B) an organohydrogenpolysiloxane having at least two hydrogen atoms bonded to silicon atoms in each molecule; (C) A thermally conductive filler comprising spherical aluminum oxide powder (C-1) having an average particle size of 80 μm or more and 120 μm or less, spherical aluminum oxide powder (C-2) having an average particle size of 60 μm or more and less than 80 μm, spherical aluminum oxide powder (C-3) having an average particle size of 25 μm or more and less than 60 μm, spherical aluminum oxide powder (C-4) having an average particle size of 5 μm or more and less than 25 μm, and spherical or irregular aluminum oxide powder (C-5) having an average particle size of 0.1 μm or more and less than 5 μm, (D) a silane coupling agent and / or a compound represented by the following general formula (1): [ka] (In the formula, R 1 are independently monovalent hydrocarbon groups; R 2 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group, or an acyl group, a is a positive number of 5 to 100, and b is an integer of 1 to 3. Organopolysiloxanes represented by the formula: (E) Platinum catalyst for hydrosilylation reaction Among the components (A) to (E), the first liquid contains the components (A), (C), (D), and (E) but does not contain the component (B); the second liquid contains the components (A), (B), (C), and (D) but does not contain the component (E); and the entire composition consisting of the first liquid and the second liquid contains 100 to 200 parts by mass of the component (D) per 100 parts by mass of the total of the components (A) and (B). and the composition contains 200 to 600 parts by mass of the component (C-1), 200 to 500 parts by mass of the component (C-2), 200 to 500 parts by mass of the component (C-3), 200 to 500 parts by mass of the component (C-4), and 300 to 700 parts by mass of the component (C-5) relative to 100 parts by mass in total of the components (A), (B), and (D), and the total of the components (C-1) to (C-5) is 1700 to 2000 parts by mass, The present invention relates to a thermally conductive two-component addition curable silicone composition, characterized in that

[0028] The present invention will be described in detail below, but the present invention is not limited thereto.

[0029] [Thermal conductive two-part addition curing silicone composition] The present invention relates to a thermally conductive two-component addition-curable silicone composition, and in particular to a thermally conductive two-component addition-curable silicone composition that has excellent thermal conductivity, easy handling, durability under high temperature and high humidity conditions, and reliability. The silicone composition of the present invention is characterized by containing the above components (A) to (E), but may contain other components as necessary. Each component will be described below.

[0030] [(A) Organopolysiloxane having at least two alkenyl groups bonded to silicon atoms in each molecule] The component (A) of the composition of the present invention is a component that serves as the main component (base polymer) of the composition. The component (A) is an organopolysiloxane having at least two alkenyl groups bonded to silicon atoms (hereinafter referred to as "silicon-bonded alkenyl groups") in one molecule, and is, for example, represented by the following average composition formula (2). The component (A) preferably has 2 to 50 silicon-bonded alkenyl groups in one molecule, and more preferably has 2 to 20 silicon-bonded alkenyl groups. These silicon-bonded alkenyl groups may be bonded to silicon atoms at the molecular chain terminals, or to silicon atoms at non-terminal locations (i.e., other than the molecular chain terminals) of the molecular chain, or a combination thereof. [ka] (In the formula, R 3 are independently an alkenyl group, R 4 are independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bonds, c is 0.0001 to 0.2, d is 1.7 to 2.2, and c+d is a number that satisfies the range of 1.90 to 2.40.

[0031] In formula (2), R 3 are independently an alkenyl group, and examples of the alkenyl group include those having 2 to 6 carbon atoms, such as a vinyl group, an allyl group, an isopropenyl group, a 1-butenyl group, a 1-pentenyl group, and a 1-hexenyl group. Among these, an alkenyl group having 2 to 4 carbon atoms is preferred, and a vinyl group is particularly preferred.

[0032] In formula (2), the remaining organic group bonded to the silicon atom is an unsubstituted or substituted monovalent hydrocarbon group R having no aliphatic unsaturated bonds. 4Examples of the monovalent hydrocarbon group include those having 1 to 12 carbon atoms, and preferably those having 1 to 6 carbon atoms. Specific examples thereof include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, hexyl, cyclohexyl, octyl, and dodecyl; aryl groups such as phenyl, 1-naphthyl, 2-naphthyl, and tolyl; aralkyl groups such as benzyl and 2-phenylethyl; and chloromethyl and 3,3,3-trifluoropropyl groups in which some or all of the hydrogen atoms of these groups are substituted with halogen atoms such as fluorine, chlorine, and bromine. From the viewpoint of ease of synthesis, etc., the methyl, phenyl, and 3,3,3-trifluoropropyl groups are preferred.

[0033] Furthermore, c is a number from 0.0001 to 0.2, and preferably a number from 0.0005 to 0.1. d is a number from 1.7 to 2.2, and preferably a number from 1.9 to 2.0. c+d is a number that satisfies 1.90 to 2.40, and preferably a number that satisfies 1.95 to 2.05.

[0034] The kinetic viscosity of component (A) at 25°C as measured by an Ostwald meter is preferably 10 to 100,000 mm 2 / s, and more preferably 100 to 50,000 mm 2 / s. This kinetic viscosity is 10 to 100,000 mm 2 When the viscosity is 100 / s, the resulting cured product has excellent strength, fluidity and workability.

[0035] Examples of organopolysiloxanes of component (A) that satisfy the above requirements include those represented by the following general formula (3): [ka] (In the formula, R 5 are independently unsubstituted or substituted monovalent hydrocarbon radicals, where R 5 At least two of the groups are alkenyl groups, and e is a number from 10 to 2,000. Examples of the above-mentioned are represented by the following formula:

[0036] In this formula (3), R 5 The unsubstituted or substituted monovalent hydrocarbon group represented by the above R 3 (alkenyl group), and R 4 (A monovalent hydrocarbon group having no aliphatic unsaturated bonds, unsubstituted or substituted), and the number of carbon atoms, specific examples, etc. are also the same. However, R 5 At least two, preferably 2 to 50, more preferably 2 to 20 of the alkenyl groups are alkenyl groups. If the number of alkenyl groups is 2 or more, the crosslink density of the resulting thermally conductive silicone cured product is sufficient. If the number of alkenyl groups is 50 or less, the crosslink density of the resulting thermally conductive silicone cured product is sufficiently high and the curability is good. Furthermore, e is preferably a number from 40 to 1,200, more preferably 50 to 600. If the number of e is 40 or more, the viscosity of the resulting thermally conductive silicone composition is sufficient, the handling workability is good, and the resulting cured product is not brittle. If the number of e is 1,200 or less, the viscosity of the resulting thermally conductive silicone composition is appropriate and the handling workability is good.

[0037] Specific examples of organopolysiloxanes represented by the above formula (3) include dimethylpolysiloxanes capped at both molecular chain terminals with dimethylvinylsiloxy groups, dimethylsiloxane-methylvinylsiloxane copolymers capped at both molecular chain terminals with trimethylsiloxy groups, dimethylsiloxane-methylvinylsiloxane copolymers capped at one molecular chain terminal with a trimethylsiloxy group and one terminal with a dimethylvinylsiloxy group, dimethylsiloxane-methylvinylsiloxane copolymers capped at both molecular chain terminals with dimethylvinylsiloxy groups, and dimethylsiloxane-diphenylsiloxane copolymers capped at both molecular chain terminals with dimethylvinylsiloxy groups.

[0038] The organopolysiloxane of component (A) may be used alone or in combination of two or more. The blending amount of component (A) in the entire composition including the first and second liquids is preferably 0.5 to 10.0 mass%, and more preferably 0.8 to 5.0 mass%.

[0039] The above-mentioned organopolysiloxanes having alkenyl groups are themselves known and can be produced by conventional methods.

[0040] [(B) Organohydrogenpolysiloxane having at least two hydrogen atoms bonded to silicon atoms in one molecule] The component (B) is an organohydrogenpolysiloxane having at least two hydrogen atoms bonded to silicon atoms (hereinafter also referred to as "silicon-bonded hydrogen atoms") in one molecule. The number of silicon-bonded hydrogen atoms in this organohydrogenpolysiloxane in one molecule is preferably 2 to 100, more preferably 2 to 50, and particularly preferably 2 to 20. If the number of silicon-bonded hydrogen atoms is too small, the crosslink density of the resulting thermally conductive silicone cured product will be too low and the product will not cure. If the number of silicon-bonded hydrogen atoms is 100 or less, the crosslink density of the resulting thermally conductive silicone cured product will be appropriate and flexible, and voids will not easily occur in the cured product due to dehydrogenation during storage or curing. The silicon-bonded hydrogen atoms may be at the molecular chain terminal, in the middle of the molecular chain, or both.

[0041] An example of the component (B) is one represented by the following average composition formula (4). [ka] (In the formula, R 6 is a hydrogen atom or an independently monovalent hydrocarbon group having no aliphatic unsaturated bonds, and f is a number from 8 to 1,000.

[0042] In the above formula (4), R 6are independently monovalent hydrocarbon groups having no aliphatic unsaturated bonds, and the number of carbon atoms is preferably 1 to 12, more preferably 1 to 6. Specific examples thereof include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, hexyl, cyclohexyl, octyl, and dodecyl; aryl groups such as phenyl, 1-naphthyl, 2-naphthyl, and tolyl; aralkyl groups such as benzyl and 2-phenylethyl; and chloromethyl and 3,3,3-trifluoropropyl groups in which some or all of the hydrogen atoms of these groups are substituted with halogen atoms such as fluorine, chlorine, and bromine. Among these, methyl, phenyl, and 3,3,3-trifluoropropyl groups are preferred from the viewpoint of ease of synthesis.

[0043] The number of silicon atoms in one molecule of the organohydrogenpolysiloxane of component (B) (i.e., degree of polymerization) is usually 8 to 1,000, but from the viewpoints of improving the handling of the composition and the properties of the resulting cured product, it is preferably 20 to 500, and more preferably 20 to 100. If the degree of polymerization is 8 or more, the viscosity of the resulting thermally conductive silicone composition is suitable, the handling is also good, and the resulting cured product is not brittle. If the degree of polymerization is 1,000 or less, the viscosity of the resulting thermally conductive silicone composition is suitable, and the handling is also good.

[0044] Furthermore, there are no particular limitations on the molecular structure of the organohydrogenpolysiloxane of component (B), so long as it satisfies the above requirements.

[0045] The viscosity of the organohydrogenpolysiloxane of component (B) is usually 1 to 10,000 mPa·s, preferably 3 to 2,000 mPa·s, and more preferably 10 to 1,000 mPa·s, and it is desirable that it is liquid at room temperature (25°C). In the present invention, unless otherwise specified, the viscosity is a value measured with a BM type viscometer (for example, manufactured by Tokyo Keiki Co., Ltd.). The rotor, rotation speed, and rotation time are appropriately selected according to the viscosity based on conventional methods.

[0046] The organohydrogenpolysiloxane of the component (B) may use either a single compound, or a combination of two or more different compounds.

[0047] This organohydrogenpolysiloxane is synthesized by a conventional method.

[0048] The amount of organohydrogenpolysiloxane in component (B) is such that there are 0.1 to 5.0 silicon-bonded hydrogen atoms (SiH groups) in component (B) per alkenyl group in component (A) in the entire composition consisting of liquids 1 and 2. A blend amount of 0.1 or more provides a sufficient effect of improving storage stability, while a blend amount of 5.0 or less provides stable physical properties for the resulting thermally conductive silicone cured product.

[0049] It should be noted that component (B) is used in liquid 2 and is not contained in liquid 1. When component (B) is used in liquid 1, liquid 1 thickens and hardens over time at room temperature, and is therefore unable to maintain the viscosity it had at the time of production.

[0050] [(C) Thermally conductive filler] Component (C) is a thermally conductive filler and consists of spherical aluminum oxide powder (C-1) having an average particle diameter of 80 to 120 μm, spherical aluminum oxide powder (C-2) having an average particle diameter of 60 to 80 μm, spherical aluminum oxide powder (C-3) having an average particle diameter of 25 to 60 μm, spherical aluminum oxide powder (C-4) having an average particle diameter of 5 to 25 μm, and spherical or crushed aluminum oxide powder (C-5) having an average particle diameter of 0.1 to 5 μm. When the range of the average particle size of components (C-1) to (C-5) is expressed as above, the range of the average particle size of component (C-1) includes both ends, but the range of the average particle size of components (C-2) to (C-5) includes the lower limit of the numerical range but does not include the upper limit. In other words, the average particle size of component (C-1) is 80 μm or more and 120 μm or less, and for example, the average particle size of component (C-2) is 60 μm or more and less than 80 μm.

[0051] The average particle size in the present invention can be measured by a laser diffraction / scattering type particle size distribution analyzer, for example, "Microtrac MT3300EX" manufactured by Nikkiso Co., Ltd. The average particle size is obtained by multiplying the measured particle size value by the relative particle amount (difference %) and dividing the result by the total relative particle amount (100%). The average particle size is the average diameter of the particles.

[0052] The average particle size of component (C-1) is 80 to 120 μm, preferably 90 to 110 μm. If the average particle size of component (C-1) is more than 120 μm, it may cause wear on the kneader and stirring blades, increase the material thickness when mounted, and increase the unevenness of the sheet surface, resulting in an increase in thermal resistivity. The spherical aluminum oxide powder of component (C-1) may be of one type or a combination of two or more types with different average particle sizes.

[0053] When the powder size is measured using a laser diffraction / scattering particle size distribution measuring device, such as a Microtrac MT3300EX manufactured by Nikkiso Co., Ltd., and expressed as a particle size distribution, and the distribution is divided into two, the particle size at which the larger side has an abundance ratio of 10% and the smaller side has an abundance ratio of 90% is taken as d90, then the d90 of component (C-1) is 90 μm or more and 170 μm or less, preferably 110 μm or more and 150 μm or less.

[0054] The average particle size of component (C-2) is 60 to 80 μm, and preferably 65 to 75 μm. As the spherical aluminum oxide powder of component (C-2), one type may be used or two or more types with different average particle sizes may be used in combination.

[0055] The average particle size of component (C-3) is 25 to 60 μm, and preferably 30 to 55 μm. As the spherical aluminum oxide powder of component (C-3), one type may be used or two or more types with different average particle sizes may be used in combination.

[0056] The average particle size of component (C-4) is 5 to 25 μm, and preferably 8 to 20 μm. As the spherical aluminum oxide powder of component (C-4), one type may be used, or two or more types with different average particle sizes may be used in combination.

[0057] The average particle size of component (C-5) is 0.1 to 5 μm, preferably 0.5 to 3 μm. If the average particle size is less than 0.1 μm, the surface area of ​​the particles increases, and the interface area between the particles and the resin increases, which increases the interfacial heat resistance, tending to deteriorate the thermal conductivity and causing a problem of a significant increase in the viscosity of the composition. As the aluminum oxide powder of component (C-5), one type or two or more types having different average particle sizes may be used in combination.

[0058] The shape of the (C-5) component is spherical or irregularly shaped aluminum oxide powder. In addition, although either spherical or irregular shapes can be used, irregular shapes are more preferable because spherical particles result in point contact between the fillers, reducing the contact area between the fillers. In other words, in the present invention, it is preferable that the (C-5) component is an irregularly shaped aluminum oxide powder. Note that shapes other than spherical are irregular. Here, spherical refers to fillers with an average circularity of 0.85 or more. The average circularity is calculated as follows. In a particle image taken with a scanning electron microscope, if the projected area (S) and perimeter (L) of a particle are taken, and the area of ​​a perfect circle corresponding to the perimeter (L) is taken as (X), the circularity of the particle can be calculated as S / X. Therefore, if we assume a perfect circle (radius r) with the same perimeter as the perimeter (L) of the sample particle, L = 2πr, X = πr 2 Therefore, X=π×(L / 2π) 2 The sphericity of each particle is given by Sphericity = S / X = S × 4π / L. 2 A circularity of 1 is a perfect circle, and the further away from a perfect circle the closer the circularity is to 0. The sphericity of 100 randomly selected particles thus obtained is determined, and the average value is taken as the average sphericity.

[0059] The amount of component (C-1) is 200 to 600 parts by mass, preferably 230 to 550 parts by mass, per 100 parts by mass of the total of components (A), (B), and (D). If the amount of component (C-1) is too small, the filling property is poor and the thermal conductivity is reduced. If the amount of component (C-1) is too large, the filling property is also poor, the viscosity is increased, and wear of the kneader and stirring blades is increased.

[0060] The amount of component (C-2) blended is 200 to 500 parts by mass, preferably 230 to 450 parts by mass, and more preferably 250 to 400 parts by mass, per 100 parts by mass of the total of components (A), (B), and (D). If the amount of component (C-2) blended is too small or too large, it becomes difficult to densely pack component (C), resulting in a decrease in thermal conductivity and an increase in viscosity.

[0061] The amount of component (C-3) is 200 to 500 parts by mass, preferably 230 to 450 parts by mass, and more preferably 250 to 400 parts by mass, per 100 parts by mass of the total of components (A), (B), and (D). If the amount of component (C-3) is too small or too large, it becomes difficult to densely pack component (C), resulting in a decrease in thermal conductivity and an increase in viscosity.

[0062] The amount of component (C-4) blended is 200 to 500 parts by mass, preferably 230 to 450 parts by mass, and more preferably 250 to 400 parts by mass, per 100 parts by mass of the total of components (A), (B), and (D). If the amount of component (C-4) blended is too small or too large, it becomes difficult to densely pack component (C), resulting in a decrease in thermal conductivity and an increase in viscosity.

[0063] The amount of the (C-5) component is 300 to 700 parts by mass, preferably 330 to 660 parts by mass, and more preferably 350 to 630 parts by mass, per 100 parts by mass of the total of the (A), (B), and (D) components. If the amount of the (C-5) component is too small, it becomes difficult to densely pack the (C) component, and oil separation increases over time. If the amount of the (C-5) component is too large, there is a problem that the viscosity of the composition increases significantly, and the thermal conductivity decreases.

[0064] The total amount of components (C-1) to (C-5) is 1700 to 2000 parts by mass, and preferably 1800 to 1900 parts by mass, per 100 parts by mass of the total of components (A), (B), and (D). If the amount is less than 1700 parts by mass, the thermal conductivity of the composition may be insufficient, and if it exceeds 2000 parts by mass, it becomes difficult to fill the thermally conductive filler.

[0065] The crystal structure of the aluminum oxide powder may be either single crystal or polycrystal, but the crystal phase is preferably the α phase from the viewpoint of high thermal conductivity, and the specific gravity is preferably 3.7 or more. If the specific gravity is 3.7 or more, the ratio of voids and low crystal phase present inside the particles is appropriate, making it easy to increase the thermal conductivity. The particle size of the aluminum oxide powder can be adjusted by classification.

[0066] From the viewpoints of thermal conductivity, moisture resistance, and packing properties, only aluminum oxide powder is suitable as the thermally conductive filler of component (C), and other thermally conductive fillers are not included.

[0067] The (C) component is used in both the first liquid and the second liquid, and the ratio of the (C) component used in the first liquid and the second liquid is not particularly limited, so long as the mixing ratio of the first liquid to the second liquid is approximately the same mass ratio.

[0068] [(D) Surface treatment agent] The component (D) is a surface treatment agent, and is a silane coupling agent and / or a compound represented by the following general formula (1): [ka] (In the formula, R 1 are independently monovalent hydrocarbon groups; R 2 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group, or an acyl group, a is a positive number of 5 to 100, and b is an integer of 1 to 3. The organopolysiloxane is represented by the formula:

[0069] The incorporation of component (D) has the effect of lowering the viscosity of the resulting silicone composition.

[0070] Examples of the silane coupling agent include vinyl-based silane coupling agents, epoxy-based silane coupling agents, acrylic-based silane coupling agents, and long-chain alkyl-based silane coupling agents, and can be used alone or in combination of two or more. For example, hexyltrimethoxysilane, decyltrimethoxysilane, hexadecyltrimethoxysilane, decylmethyldimethoxysilane, decyldimethylmethoxysilane, decyltriethoxysilane, 7-octenyltrimethoxysilane, phenyltrimethoxysilane, and the like can be mentioned, with decyltrimethoxysilane being particularly preferred.

[0071] In the above formula (1), R 1 are independently unsubstituted or substituted monovalent hydrocarbon groups having preferably 1 to 10 carbon atoms, more preferably 1 to 6, and even more preferably 1 to 3 carbon atoms, and specific examples thereof include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, cyclohexyl, octyl, and dodecyl; aryl groups such as phenyl; and groups in which some or all of the hydrogen atoms have been substituted with halogen atoms such as fluorine, chlorine, and bromine, or with a cyano group, such as a chloromethyl group, a 3,3,3-trifluoropropyl group, or a cyanoethyl group. 1 As the alkyl group, a methyl group, a phenyl group, and a 3,3,3-trifluoropropyl group are preferable.

[0072] In the above general formula (1), R 2 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group, or an acyl group. Examples of the alkyl group include the above R 3Examples of the alkoxyalkyl group include the same straight chain alkyl group, branched chain alkyl group, and cyclic alkyl group as those exemplified in . Examples of the alkoxyalkyl group include a methoxyethyl group, a methoxypropyl group, and the like, and preferably those having 2 to 10 carbon atoms. Examples of the alkenyl group include a vinyl group, an allyl group, an isopropenyl group, a 1-butenyl group, a 1-pentenyl group, and a 1-hexenyl group, and preferably those having 1 to 8 carbon atoms. Examples of the acyl group include an acetyl group, an octanoyl group, and the like, and preferably those having 2 to 10 carbon atoms. R 2 is preferably an alkyl group, and particularly preferably a methyl group or an ethyl group.

[0073] In addition, a is a number from 5 to 100, and preferably a number from 8 to 50; b is a number from 1 to 3, and preferably 3.

[0074] Specific examples of suitable organopolysiloxanes of component (D) include the following: [ka] (In the formula, Me is a methyl group. The same applies hereinafter.)

[0075] The viscosity of the organopolysiloxane of component (D) at 25°C is typically 0.01 to 30 Pa·s, and preferably 0.1 to 10 Pa·s. If the viscosity is 0.01 Pa·s or more, oil bleeding of component (D) from the silicone composition is unlikely to occur. If the viscosity is 30 Pa·s or less, the resulting silicone composition has good fluidity and is easy to apply.

[0076] In the present invention, when the component (D) is used, it is preferable to heat-treat the mixture together with the above-mentioned component (C) or components (A) to (C) at a temperature of 70° C. or higher, more preferably at a temperature of 80 to 180° C.

[0077] In the present invention, when the (D) component is used, the above-mentioned (C) component can be pretreated with the (D) component. By treating the (C) component with the (D) component, the effect of lowering the viscosity of the resulting silicone composition can be obtained. In this case, the surface treatment method of the (C) component with the (D) component can be a spray method using a fluid nozzle, a stirring method with shear force, a dry method such as a ball mill or mixer, or a wet method such as a water-based or organic solvent-based method. The stirring is performed to a degree that does not cause destruction of the thermally conductive filler. The temperature in the system or the drying temperature after the treatment in the dry method is appropriately determined in a range where the surface treatment agent does not volatilize or decompose depending on the type of the surface treatment agent, and is, for example, 80 to 180°C.

[0078] When the (D) component is used, the blending amount is 100 to 200 parts by mass, preferably 110 to 190 parts by mass, and more preferably 120 to 180 parts by mass, per 100 parts by mass of the total of the (A) and (B) components. If the blending amount is less than 100 parts by mass, the effect of reducing the viscosity is small. Furthermore, in a two-liquid addition curing material, dehydrogenation of the organohydrogenpolysiloxane occurs due to the thermally conductive filler during storage at room temperature. Therefore, if the amount of the silane coupling agent or the organopolysiloxane having an alkoxy group at one end is too small, the change over time in which the hardness decreases during storage at room temperature cannot be suppressed. If the blending amount is more than 200 parts by mass, the hardness of the cured sheet under moisture-resistant conditions tends to increase, and the elongation decreases, resulting in a material with poor reliability. The blending amount of the (D) component in the entire composition including the first and second liquids is preferably 1.5 to 4.7% by mass, and more preferably 2.0 to 3.5% by mass.

[0079] The component (D) is used in both the first and second liquids. The ratio of the component (D) used in the first and second liquids is not particularly limited, but for example, the same amount of the component (D) can be used in the first and second liquids. Also, the ratio can be set according to the component (C) in each liquid.

[0080] [(E) Platinum group metal catalyst] The component (E) of the composition of the present invention is a platinum group metal catalyst, which is a catalyst that promotes the addition reaction between the alkenyl group in the component (A) and the hydrogen atom bonded to the silicon atom in the component (B).For example, chloroplatinic acid, alcohol-modified chloroplatinic acid, coordination compounds of chloroplatinic acid with olefins, aldehydes, vinylsiloxanes, or acetylene compounds, tetrakis(triphenylphosphine)palladium, chlorotris(triphenylphosphine)rhodium, etc. are used, but platinum catalysts are preferred, and coordination compounds of chloroplatinic acid and vinylsiloxane are most preferred.

[0081] The amount of component (E) may be a catalytic amount, but is usually an amount that is 0.1 to 500 ppm, preferably 1 to 100 ppm, calculated as the mass of platinum group metal based on the total composition consisting of liquids 1 and 2. It is preferable to keep the amount of component (E) within this range because appropriate curing properties can be obtained.

[0082] The component (E) is used in the first liquid and is not contained in the second liquid.

[0083] [others] In addition to the above-mentioned components (A) to (E), the composition of the present invention may contain various additives known per se, as necessary. Examples of other additives are listed below.

[0084] For example, reaction regulators for adjusting the curing rate and storage stability, specifically acetylene alcohols such as triallyl isocyanate alkyl maleate, ethynyldecyl methyl carbinol, ethynylcyclohexanol, and the like, and silanes thereof, siloxane modified products, hydroperoxides, tetramethylethylenediamine, colorants such as ferrous oxide and ferric oxide, either alone or in combination, and thixotropic agents such as fumed silica, can be blended. The blending amount of each of these is preferably 0.01 to 100,000 ppm by mass per the present composition.

[0085] The mixing device used in preparing the composition may be a known mixer such as a static mixer, a planetary mixer, or a paddle mixer.

[0086] [Manufacturing method] The composition of the present invention is a thermally conductive two-part addition-curable silicone composition consisting of a first part which contains the above-mentioned components (A), (C), (D), and (E) but does not contain the above-mentioned component (B), and a second part which contains the above-mentioned components (A), (B), (C), and (D) but does not contain the above-mentioned component (E).

[0087] The method for producing the composition of the present invention may involve mixing the components of the first and second liquids, and the first liquid may be produced, for example, by a method having the following steps. A step of mixing the components (A), (C), and (D) and heat-treating the mixture at a temperature of 70° C. or higher to obtain a heated mixture; A process in which the heated mixture obtained above is cooled to room temperature (25°C) or below, and then component (E), a reaction regulator, a colorant, and a thixotropic agent are added. The second liquid is a step of mixing the components (A), (C), and (D) and heating the mixture at a temperature of 70° C. or higher to obtain a heated mixture; A process in which the heated mixture obtained above is cooled to room temperature (25°C) or below, and then component (B), a reaction regulator, a colorant, and a thixotropic agent are added.

[0088] The heating temperature in the heat treatment step is preferably 70°C or higher, more preferably 70 to 180°C. The heating time is not particularly limited, and is preferably 1 hour or more, more preferably 1 to 3 hours. When an additive is added, it may be added in any step, but it is preferably added after cooling the heated mixture. As a mixing device for preparing the above composition, a known mixer such as a static mixer, a planetary mixer, or a paddle mixer can be used.

[0089] In the present invention, it is preferable that each of the first liquid and the second liquid has a viscosity at 25° C. of 30 to 800 Pa·s when measured with a spiral viscometer at a rotation speed of 10 rpm.

[0090] The viscosity of the composition of the present invention at 25°C is 30 to 800 Pa·s, preferably 70 to 400 Pa·s, for each of the first and second liquids, measured using a spiral viscometer: Malcom viscometer (Type PC-10AA, rotation speed 10 rpm). If the viscosity is 30 Pa·s or more, the shape retention of the composition is sufficient, and if it is 800 Pa·s or less, workability is not difficult. In the present invention, the viscosity can be set within the above range by setting the blending amount and blending ratio of component (C) within the range specified above.

[0091] The thermal conductivity of the composition of the present invention is preferably 5.5 W / m·K or more, and more preferably 5.7 W / m·K or more, as measured by the hot disk method in accordance with ISO 22007-2. If the thermal conductivity is 5.5 W / m·K or more, the heat dissipation performance of heat-generating electronic components will be sufficient. There is no particular upper limit to the thermal conductivity, but it is preferably 6.9 W / m·K or less, and more preferably 6.7 W / m·K or less. In the present invention, the thermal conductivity can be set within the above range by setting the blending amount and blending ratio of component (C) within the range specified above.

[0092] The present invention provides a thermally conductive sheet obtained by curing the above-mentioned thermally conductive two-part addition curable silicone composition. For example, a thermally conductive sheet can be obtained by mixing the above-mentioned first and second liquids of the composition of the present invention in an arbitrary mixing ratio, molding the mixture, and leaving it at room temperature or heating it at 40 to 200° C. However, the mixing ratio by weight is preferably first liquid:second liquid=130:100 to 100:130, and more preferably first liquid:second liquid=110:100 to 100:110.

[0093] The properties of the thermal conductive sheet are not limited, but may be, for example, gel, low hardness rubber, or high hardness rubber, and is preferably low hardness rubber. In this case, low hardness refers to a value measured by a Shore OO hardness tester specified in ASTM D 2240-05 of 20 to 80, preferably 30 to 70. If the hardness is 20 or more, the heat dissipation material is less likely to shift or fall off from the mounted position due to impact such as vibration after mounting. Also, if the hardness is 80 or less, the stress applied to the electronic components is not large, and there is no adverse effect on the solder life.

[0094] Thus, the present invention provides a cured product of the above-mentioned thermally conductive two-part addition curable silicone composition, characterized in that the hardness of the sheet-like cured product obtained by curing the above-mentioned thermally conductive two-part addition curable silicone composition is in the range of 20 to 80, as measured using a Shore OO hardness tester as specified in ASTM D 2240-05.

[0095] Regarding the elongation of the sheet-like cured product (thermal conductive sheet) obtained by curing the composition of the present invention, the elongation at break measured by a tensile test specified in JIS K 7161 using a tensile No. 2 dumbbell-shaped tensile test piece conforming to JIS K 6251 is preferably 20% or more. If the elongation is 20% or more, the heat dissipation material can follow the warping of the electronic component when heat is applied to the electronic component after mounting. There is no particular upper limit to the elongation, but it is preferably 70% or less.

[0096] The thickness of the sheet is not particularly limited, but is preferably 150 μm or more, and in consideration of the size of the electronic components to be mounted, is preferably 5 mm or less.

[0097] The present invention also provides a cured product of the above-mentioned thermally conductive two-component addition curable silicone composition, characterized in that the hardness of the sheet-like cured product obtained by curing the above-mentioned thermally conductive two-component addition curable silicone composition is such that after being subjected to 85°C / 85% RH for 1000 hours, the elongation at break measured in a tensile test specified in JIS K 7161 using a tensile No. 2 dumbbell-shaped tensile test piece conforming to JIS K 6251 is 10% or more. The elongation at break is preferably 20% or more. The elongation after the humidity resistance test can be controlled to fall within the above range by adjusting the blending amount of the component (D) within the range specified above.

[0098] A thermally conductive sheet as described above has high thermal conductivity and suppresses the increase in hardness and decrease in elongation of the cured product due to moisture-resistant conditions, and is therefore useful as an excellent heat dissipation material for heat-generating electronic components. EXAMPLES

[0099] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0100] Component (A) A-1: Dimethyl polysiloxane with both ends blocked by dimethylvinylsiloxy groups (dynamic viscosity 400 mm 2 / s, the amount of Vi group per 100 g is 0.0185 mol, and e in general formula (3) is 146)

[0101] (B) Component B-1: Trimethylsiloxy-blocked methylhydrogen-dimethylpolysiloxane (Si-H content 0.00128 mol / g) represented by formula (5) [ka]

[0102] B-2: Dimethylhydrogensiloxy-blocked dimethylpolysiloxane represented by formula (6) (Si-H content: 0.00130 mol / g) [ka]

[0103] (C) Component C-1-1: Spherical aluminum oxide (average particle size 100 μm, density 3.98 g / cm 3 ) C-2-1: Spherical aluminum oxide (average particle size 70 μm, density 3.98 g / cm 3 ) C-3-1: Spherical aluminum oxide (average particle size 45 μm, density 3.98 g / cm 3 ) C-4-1: Spherical aluminum oxide (average particle size 10 μm, density 3.98 g / cm 3 ) C-5-1: Spherical aluminum oxide (average particle size 3 μm, density 3.98 g / cm 3 ) C-5-2: irregular aluminum oxide (average particle size 1.2 μm, density 3.98 g / cm 3 ) (For comparison) C-6-1: Spherical aluminum oxide (average particle size 150 μm, density 3.98 g / cm 3 )

[0104] (D) Component D-1: Organopolysiloxane represented by formula (7) [ka]

[0105] (E) Component E-1: Vinylsiloxane complex of chloroplatinic acid (Pt content 1% by mass)

[0106] 1st liquid Components (A), (C) and (D) were added to a 5L planetary mixer manufactured by Inoue Seisakusho Co., Ltd. in the mass mixing ratios shown in Tables 1 to 3 and mixed. The mixture was then heat-treated and mixed at 150° C. for 1 hour to obtain mixture 1. Next, this mixture 1 was sufficiently cooled to room temperature (25°C), and then component (E) was added in the mass mixing ratios in Tables 1 to 3 below and mixed uniformly at room temperature (25°C) for 20 minutes to obtain a first liquid.

[0107] 2nd liquid Components (A), (C) and (D) were added to a 5L planetary mixer manufactured by Inoue Seisakusho Co., Ltd. in the mass mixing ratios shown in Tables 1 to 3 and mixed. The mixture was then heat-treated and mixed at 150° C. for 1 hour to obtain mixture 2. Next, this mixture 2 was sufficiently cooled to room temperature (25°C), and then component (B) was added in the mass mixing ratios in Tables 1 to 3 below and mixed uniformly at room temperature (25°C) for 20 minutes to obtain a second liquid.

[0108] viscosity The viscosity of each of the first and second liquids in each example was measured at 25° C. using a spiral viscometer: Malcom viscometer (type PC-10AA, rotation speed 10 rpm).

[0109] Thermal Conductivity The first and second liquids of each example were mixed and discharged at room temperature (25°C) using a static mixer MXA6.3-21 (manufactured by Noritake Co., Limited) so as to be uniform in a mass ratio of 1:1. The mixture was then thoroughly degassed in a vacuum and poured into a mold so that the thickness after curing would be 6 mm. The mixture was then cured at 25°C for 24 hours to obtain a sheet-like cured product. The thermal conductivity of the obtained cured product was measured at 25° C. using a hot disc method thermal property measuring device TPS 2500 S (manufactured by Kyoto Electronics Manufacturing Co., Ltd.) (hot disc method in accordance with ISO 22007-2).

[0110] Hardness The first and second liquids of each example were mixed and discharged at room temperature (25°C) using a static mixer MXA6.3-21 (manufactured by Noritake Co., Limited) so as to be uniform in a mass ratio of 1:1. The mixture was then thoroughly degassed in a vacuum and poured into a mold so that the thickness after curing would be 6 mm. The mixture was then cured at 25°C for 24 hours to obtain a sheet-like cured product. The hardness of the resulting cured product was measured using a Shore OO hardness tester as specified in ASTM D 2240-05, and the value measured 30 seconds after the start of the measurement was recorded.

[0111] Moisture resistance test The first and second liquids of Example 1 and Comparative Example 1 were mixed and discharged at room temperature (25°C) using a static mixer MXA6.3-21 (manufactured by Noritake Co., Ltd.) so as to be uniform in a mass ratio of 1:1, and then thoroughly degassed in vacuum before being poured into a mold having a thickness of 2 mm after curing, and cured at 25°C for 24 hours to obtain a sheet-like cured product. The thermally conductive silicone cured product was then stored in a thermo-hygrostat at 85°C / 85%RH and aged for 1000 hours. After 1000 hours, the silicone cured product was removed. Dumbbell-shaped tensile test pieces in accordance with JIS K 6251 were punched out from the cured products before and after aging, and the elongation of the test pieces was measured by a tensile test specified in JIS K 7161 to measure the elongation at break.

[0112] The results of the viscosity, thermal conductivity, and hardness are shown in Tables 1 to 3, and the results of the moisture resistance test are shown in Table 4. In the tables, "H / Vi" represents the molar ratio of silicon-bonded hydrogen atoms (SiH groups) in component (B) to one alkenyl group in component (A) in the entire composition consisting of the first and second liquids combined.

[0113] [Table 1]

[0114] [Table 2]

[0115] [Table 3]

[0116] [Table 4]

[0117] From the above results, in the case of the thermally conductive two-part addition curing silicone compositions of Examples 1 to 7 of the present invention, a sheet-shaped cured product was obtained with a thermal conductivity in the above-mentioned preferred range of 5.5 to 6.9 W / m·K in the hot disk method according to ISO 22007-2, and showed excellent thermal conductivity properties. In addition, the viscosity of each of the first and second parts of the thermally conductive silicone composition and the hardness of the sheet-shaped cured product were also suitable values ​​for a heat dissipation material for heat-generating electronic components (Tables 1 and 2). Furthermore, as shown in Table 4, in Example 1, in which the content of component (D) is appropriate, the decrease in elongation after 1000 hours of storage at 85°C / 85% RH is suppressed, while in Comparative Example 1, in which the content of component (D) is excessive, the elongation is greatly decreased under moisture-resistant conditions, and it is found that the reliability is poor. In addition, from Comparative Example 2, it is found that sufficient thermal conductivity cannot be obtained when component (C-1) is not included (Table 2). It can be seen that in Comparative Example 3, when the particle size of component (C-1) is large (containing component (c-6-1) with a larger particle size instead), and in Comparative Example 4, when the amount of component (D) is too small, the viscosity increases so significantly that it cannot be measured (Tables 2 and 3). Furthermore, it can be seen that in Comparative Example 5, the viscosity also increases when the amount of component (C-1) is large and the amount of component (C-5) is small. It can be seen that in Comparative Example 6, when the amount of component (C-1) is small and the amount of component (C-5) is excessive, sufficient thermal conductivity cannot be obtained. Thus, according to the present invention, a thermally conductive silicone composition and its cured product having high thermal conductivity and high reliability under moisture-resistant conditions can be obtained. [Industrial Applicability]

[0118] The thermally conductive silicone composition obtainable by the present invention has particularly excellent thermal conductivity and is easy to handle, and also has excellent durability and reliability under high-temperature, high-humidity conditions, and is therefore expected to improve reliability in applications where it is used for heat dissipation and protection of electronic components such as power devices, transistors, thyristors, CPUs (central processing units), and GPUs (graphics processing units).

[0119] The present specification includes the following aspects. [1]: A thermally conductive two-part addition curable silicone composition consisting of a first part and a second part, (A) an organopolysiloxane having at least two alkenyl groups bonded to silicon atoms in each molecule; (B) an organohydrogenpolysiloxane having at least two hydrogen atoms bonded to silicon atoms in each molecule; (C) A thermally conductive filler comprising spherical aluminum oxide powder (C-1) having an average particle size of 80 μm or more and 120 μm or less, spherical aluminum oxide powder (C-2) having an average particle size of 60 μm or more and less than 80 μm, spherical aluminum oxide powder (C-3) having an average particle size of 25 μm or more and less than 60 μm, spherical aluminum oxide powder (C-4) having an average particle size of 5 μm or more and less than 25 μm, and spherical or irregular aluminum oxide powder (C-5) having an average particle size of 0.1 μm or more and less than 5 μm, (D) a silane coupling agent and / or a compound represented by the following general formula (1): [ka] (In the formula, R 1 are independently monovalent hydrocarbon groups; R 2 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group, or an acyl group, a is a positive number of 5 to 100, and b is an integer of 1 to 3. Organopolysiloxanes represented by the formula: (E) Platinum catalyst for hydrosilylation reaction Among the components (A) to (E), the first liquid contains the components (A), (C), (D), and (E) but does not contain the component (B); the second liquid contains the components (A), (B), (C), and (D) but does not contain the component (E); and the entire composition consisting of the first liquid and the second liquid contains 100 to 200 parts by mass of the component (D) per 100 parts by mass of the total of the components (A) and (B). and the composition contains 200 to 600 parts by mass of the component (C-1), 200 to 500 parts by mass of the component (C-2), 200 to 500 parts by mass of the component (C-3), 200 to 500 parts by mass of the component (C-4), and 300 to 700 parts by mass of the component (C-5) relative to 100 parts by mass in total of the components (A), (B), and (D), and the total of the components (C-1) to (C-5) is 1700 to 2000 parts by mass, 1. A thermally conductive two-component addition-curable silicone composition comprising: [2]: The thermally conductive two-component addition curable silicone composition according to [1], characterized in that the viscosity of each of the first and second liquids at 25°C is 30 to 800 Pa s when measured with a spiral viscometer at a rotation speed of 10 rpm. [3]: The thermally conductive two-component addition-curable silicone composition according to [1] or [2], wherein the component (C-5) is an irregularly shaped aluminum oxide powder. [4]: A cured product of the thermally conductive two-part addition curable silicone composition according to any one of [1] to [3], wherein the hardness of the sheet-shaped cured product obtained by curing the thermally conductive two-part addition curable silicone composition is in the range of 20 to 80 as measured by a Shore OO hardness tester according to ASTM D 2240-05. [5]: A cured product of the thermally conductive two-component addition curable silicone composition according to any one of [1] to [3], characterized in that the hardness of the sheet-shaped cured product obtained by curing the thermally conductive two-component addition curable silicone composition is such that after being subjected to 85°C / 85% RH for 1000 hours, the elongation at break measured by the tensile test specified in JIS K 7161 using a tensile test piece of type 2 dumbbell conforming to JIS K 6251 is 10% or more. [6]: A thermally conductive sheet, characterized by being obtained by curing any one of the thermally conductive two-component addition curing silicone compositions [1] to [3].

[0120] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention.

Claims

1. A thermally conductive two-part addition curable silicone composition comprising a first part and a second part, (A) an organopolysiloxane having at least two alkenyl groups bonded to silicon atoms in each molecule; (B) an organohydrogenpolysiloxane having at least two hydrogen atoms bonded to silicon atoms in each molecule; (C) A thermally conductive filler comprising a spherical aluminum oxide powder (C-1) having an average particle size of 80 μm or more and 120 μm or less, a spherical aluminum oxide powder (C-2) having an average particle size of 60 μm or more and less than 80 μm, a spherical aluminum oxide powder (C-3) having an average particle size of 25 μm or more and less than 60 μm, a spherical aluminum oxide powder (C-4) having an average particle size of 5 μm or more and less than 25 μm, and a spherical or irregularly shaped aluminum oxide powder (C-5) having an average particle size of 0.1 μm or more and less than 5 μm, (D) a silane coupling agent and / or a compound represented by the following general formula (1): 【Chemistry 1】 (In the formula, R 1 are independently monovalent hydrocarbon groups; R 2 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group, or an acyl group, a is a positive number from 5 to 100, and b is an integer from 1 to 3. Organopolysiloxanes represented by the formula: (E) Platinum catalyst for hydrosilylation reaction Among the components (A) to (E), the first liquid contains the components (A), (C), (D), and (E) but does not contain the component (B); the second liquid contains the components (A), (B), (C), and (D) but does not contain the component (E); and the entire composition consisting of the first liquid and the second liquid contains 100 to 200 parts by mass of the component (D) per 100 parts by mass of the total of the components (A) and (B), and the total of the (C-1) to (C-5) components is 1,700 to 2,000 parts by mass, the total of the (C-1) to (C-5) components is 200 to 600 parts by mass, the (C-2) component is 200 to 500 parts by mass, the (C-3) component is 200 to 500 parts by mass, the (C-4) component is 200 to 500 parts by mass, and the (C-5) component is 300 to 700 parts by mass, relative to 100 parts by mass in total of the (A) component, the (B) component, and the (D) component.

1. A thermally conductive two-part addition-curable silicone composition comprising:

2. The thermally conductive two-component addition curable silicone composition according to claim 1, characterized in that the first liquid and the second liquid each have a viscosity of 30 to 800 Pa s at 25°C when measured with a spiral viscometer at a rotation speed of 10 rpm.

3. The thermally conductive two-part addition curable silicone composition according to claim 1, wherein the component (C-5) is an irregularly shaped aluminum oxide powder.

4. A cured product of the thermally conductive two-part addition curable silicone composition according to any one of claims 1 to 3, wherein the hardness of the sheet-like cured product obtained by curing the thermally conductive two-part addition curable silicone composition is in the range of 20 to 80 as measured using a Shore OO hardness tester as specified in ASTM D 2240-05.

5. 4. A cured product of the thermally conductive two-part addition curable silicone composition according to any one of claims 1 to 3, characterized in that the hardness of the sheet-like cured product obtained by curing the thermally conductive two-part addition curable silicone composition is such that after being subjected to 85°C / 85% RH for 1000 hours, the elongation at break of the cured product is 10% or more as measured by a tensile test specified in JIS K 7161 using a No. 2 dumbbell-shaped tensile test piece conforming to JIS K 6251.

6. A thermally conductive sheet obtained by curing the thermally conductive two-part addition curing type silicone composition according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Two-liquid addition reaction curable heat release silicone composition and manufacturing method therefor

    JP2019131734A

  • Thermally conductive silicone potting composition

    JP2022536577A

  • Thermally conductive silicone composition and thermally conductive member

    WO2022075434A1

  • JP1975085050A

  • Water-erasable lead for solid charlk and pencil

    JP1982055977A